EFEKTIVITAS HASIL PENGELOLAAN KEKAYAAN DAERAH YANG DIPISAHKAN TAHUN 2017-2019 DI KOTA BANDUNG - Muhamad Rafi Firdaus; Husen Saeful Anwar; Ibnu Malik (Sekolah Tinggi Pariwisata Mataram, 2022)
This study describes how effective the results of regional wealth management are separated from the city of Bandung. Of the three targets for revenue sources from the management of regional wealth which are separated, there is only one post which is part of the original regional income, namely the share of profit on capital participation. The research method used by the researcher is descriptive qualitative. Data collection techniques were carried out by observation, interviews, document studies and audi visuals. The data analysis technique was carried out by data reduction, data display, and conclusion drawing/verification. The researchers conducted in-depth interviews using a purposeful sampling technique where the researchers conducted interviews with the Head of the Bandung City BPKA and Head of Sub. Bandung City BPKA Revenue Accounting. The results of the study indicate that the effectiveness of the results of regional wealth management which is separated from the city of Bandung has not yet been achieved.